1961
DOI: 10.1113/expphysiol.1961.sp001556
|View full text |Cite
|
Sign up to set email alerts
|

ESTERIFICATION OF 14C‐LABELLED CHOLESTEROL BY RETICULO‐ENDOTHELIAL CELLS

Abstract: 14C-labelled cholesterol injected intraperitoneally into rats was shown to be taken up by the reticulo-endothelial cells of the sternal lymph nodes and partly converted into 14C-labelled cholesteryl ester. The specific activity of the 14C_ labelled cholesterol in the nodes fell rapidly, while that of the 14C-labelled cholesteryl ester formed remained relatively high, suggesting that esterification of the cholesterol and its fixation as cholesteryl ester was brought about by reticulo-endothelial cells. It was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1961
1961
1984
1984

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…CHOLESTEROL suspensions taken up by reticulo-endothelial cells in rat lymph nodes or by rabbit macrophages in vitro, are partially converted to cholesterol ester [Day and French, 1959;Day and Gould-Hurst, 1961]. The fatty acid pattern of cholesterol esters may also influence their subsequent metabolism [Klein and Martin, 1959;Lewis et at., 1961] and much interest has arisen concerning fatty acid patterns of cholesterol esters in various situations, particularly in the arterial wall in atherosclerosis [Sinclair, 1956;Bottcher et al, 1960].…”
mentioning
confidence: 99%
“…CHOLESTEROL suspensions taken up by reticulo-endothelial cells in rat lymph nodes or by rabbit macrophages in vitro, are partially converted to cholesterol ester [Day and French, 1959;Day and Gould-Hurst, 1961]. The fatty acid pattern of cholesterol esters may also influence their subsequent metabolism [Klein and Martin, 1959;Lewis et at., 1961] and much interest has arisen concerning fatty acid patterns of cholesterol esters in various situations, particularly in the arterial wall in atherosclerosis [Sinclair, 1956;Bottcher et al, 1960].…”
mentioning
confidence: 99%
“…'4C-LABELLED cholesterol taken up by reticulo-endothelial cells is readily converted to 14C-labelled cholesteryl ester and evidence has been obtained that such esterification may fix the cholesterol in these cells [Day and Gould-Hurst, 1961]. It has also been shown that the uptake of cholesterol by reticulo-endothelial cells is followed by the accumulation, either by synthesis or deposition, of phospholipid and esterified fatty acids in the cells [Day, 1960 a].…”
mentioning
confidence: 99%